Pengaruh terapi Modalitas : Senam lansia Terhadap Depresi Pada Lansia di Panti Sosial Lansia Harapan Kita Palembang - Ridwan; Indra Febriani (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Background One of the therapeutic uses of the Elderly Gym Modality is used for someone who has depression, the results may be different if the elderly are actively involved in a specially designed series of exercise activities. Gradually elderly sadness are resolved through developing happy experiences. the effectiveness of elderly gymnastics therapy as a therapeutic tool will occur if the therapist has sufficient skills to make exercise the right tool. The purpose of this study was to determine the effect of therapy modalities: elderly exercise on depression in the elderly at the Harapan Kita Social Home for the Elderly in Palembang in 2020. This research method is a Quasi-Experimental research with the design used is a "one group pre-test-post test" design. The sample was 33 samples by total sampling that met the requirements, and all of them were measured the reduction of depression before and after exercise. The effect of elderly exercise on depression reduction using the –test test. Result average depression before 15.67 at 95% CI 13.74-17.59 became 14.55, at 95% CI 12.99-16.10 and the Depression Level in the Elderly depression from 7 people to 2 people from the statistical test of the test. The t-test result is a p-value of 0.007 (<0.05). The conclusion is that exercise in the elderly can reduce the level of depression in the elderly at the Harapan Kita Social Institution. Suggestion It is hoped that the orphanage will increase the activity or exercise to reduce depression in the elderly who suffer from depression